The Effects of Three Different Background Music between Vocal, Instrumental and Silent on Verbal and Spatial Task Performance in Learning - Norazirah binti Buang; Amalina Ulya; Sousan Naseri (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2019)
The objective of this study is to investigate the effect of three different backgrounds of music vocal, instrumental and silent on the verbal and spatial task performance in learning. The samples from Master students of Education in University Putra Malaysia which consisted of 36 students from Faculty of Educational Studies. This experimental research design to test hypothesis the effect of three different backgrounds of music vocal, instrumental and silent on the verbal and spatial task performance in learning. Data was analyse using IBM Statistics where this study used independent sample T-test and two-way analysis variance (ANOVA). The T-test result of analysis show there is differences between vocal condition (t = 1.101, p = 0.172), instrumental condition (t = 2.06, p = 0.018), and silent condition difference (t = 2.712, p = 0.022) on the verbal and spatial task in learning. Two-way ANOVA Task-Music group Greenhouse-Geisserwas reported in the significant level (p0.05).